CITIZEN JOURNALISM: KELAYAKAN BERITA DITINJAU DARI SEGI BAHASA DAN ETIKA JURNALISTIK - Anhar Fazri (SOURCE : Jurnal Ilmu Komunikasi, 2016)
The era of journalism today increasingly provide freedom for all people who want to present the results of the journalistic works, namely with a growing phenomenon of citizen journalism. However, the problems that occur, namely the citizen journalism that has not yet entirely understand how to issue a code of conduct and also grammar in presenting a news so it will give an assessment about the worth or whether a news. The development of the concept of citizen journalism originated from the emergence of the internet world. However, that does not mean such conservation media print and electronic media cannot accommodate the writings that are the result of a process of citizen journalism. In addition to the electronic and print media, the current online media also continues to develop and provide a place for who want to create news reports they do, such as kompasiana.com, tribun Yogya and other. The results of the citizen journalism reports sent to the mass media by way of via email. The number of communities that ultimately plunging into a citizen journalist, raises a big question, whether they produce news later deserve to be consumed using the theory of community news, Citizen Journalism and the Ethics of journalism Indonesia.Keywords: Feasibility News, Citizen Journalism, Journalism Code of Ethics